Residential Mobility, Transience, Depression, and Marijuana Use Initiation Among Adolescents and Young Adults - Cristie Glasheen; Valerie L Forman-Hoffman; Jason Williams (SAGE Publishing, 2017)
Marijuana use initiation is associated with numerous health and behavioral consequences, particularly among young adolescents. Finding easily identifiable risk markers for marijuana initiation is an important step for targeting primary and secondary prevention efforts. This study used data from the 2010-2014 National Survey on Drug Use and Health to evaluate the association between residential mobility (no mobility, low mobility, high mobility [ie, transience]), and major depressive episode(s) (MDE) on marijuana initiation among adolescents (12-17) and young adults (18-20). Age-stratified logistic regression models indicated that among 12- to 13-year-old adolescents, mobility in the past 5 years and past year MDE have a multiplicative effect on the odds of past year marijuana initiation. Among adolescents aged 14 to 15 years, both mobility and MDE were independently associated with marijuana initiation, but there was no interaction. Among older adolescents (aged 16-17 years), only transience (⩾3 moves in the past 5 years) was associated with marijuana use initiation, and although MDE was significantly associated with marijuana initiation, there was no interaction with mobility. Among young adults, mobility was not associated with marijuana initiation. Residential mobility among young adolescents is an easily identifiable risk marker that may serve as an indicator for physical and mental health professionals, school personnel, and parents to use in targeting both depression and marijuana prevention efforts.